A phase III, randomized, controlled, superiority trial evaluating the fibrin pad versus standard of care in controlling parenchymal bleeding during elective hepatic surgery. Issue 1 (16th October 2012) - Koea, Jonathan B; Batiller, Jonathan; Patel, Babahai; Shen, Jessica; Hammond, Jeffrey; Hart, James; Fischer, Craig; Garden, O James
Abstract Introduction Haemostasis after liver resection may be difficult to achieve as a result of the presence of challenging bleeding, the anatomic landscape of the liver and the quality of tissue making up the hepatic parenchyma. The fibrin pad (FP) is a topical absorbable haemostat designed to be effective in a variety of tissues and across multiple bleeding intensities. This is the first clinical trial to evaluate the hemostat's safety and effectiveness in controlling bleeding during elective hepatic resection. Methods This prospective, randomized, controlled superiority trial enrolled 104 subjects undergoing elective hepatectomy in 5 countries. After parenchymal transection, subjects with an appropriately defined target bleeding site (TBS) were stratified according to the type of hepatic parenchyma and immediately randomized 1:1: FP versus Standard of Care (SoC). SoC comprised manual compression with the use of an approved topical absorbable haemostat. The primary endpoint was haemostasis at 4 min from identification of the TBS, with no re‐bleeding requiring re‐treatment prior to abdominal closure. Results were stratified for both normal and abnormal (steatosis or cirrhosis) hepatic parenchyma. All subjects were followed for 60 days post‐operatively. Results The intent‐to‐treat (ITT) analysis showed an overall treatment difference of 53.0% (P < 0.001), 82.5% (33/40 FP) versus 29.5% (13/44 SoC) in achieving haemostasis at 4 min with no re‐bleeding requiring treatment up to wound closure. The per protocol analysis showed an overall treatment difference of 65.7% (P < 0.001), with 33/35 successes (94.3%) in the FP group and 12/42 in the SoC group (28.6%). The stratification results showed treatment differences between the normal parenchyma group, 63.6% (95.8% FP versus 32.3% SoC P < 0.001) and a larger difference of 72.7% in the abnormal parenchyma group (90.9% FP versus 18.2% SoC P = 0.0003). Post‐operative intra‐abdominal fluid collections were less frequent in the FP group (3.4% FP versus 13.3% SoC P = 0.059). There was no difference in the safety profile between the FP or SoC groups. Conclusions The FP is safe and effective when used as an adjunct to achieve haemostasis during hepatic surgery. The success rate of achieving haemostasis with a FP remained high compared with the SOC group, especially in steatotic or cirrhotic liver tissue where the control success rates diminish. In addition, FP treatment of hepatic parenchymal surfaces may reduce the risk of post‐operative biliary and fluid collections.